2015
DOI: 10.1007/s00436-015-4600-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gold nanoparticles on brain of mice infected with Schistosoma mansoni

Abstract: Schistosomiasis is a condition characterized by high rates of morbidity and cognitive impairment. It afflicts many people in tropical and sub-tropical countries. Our study aimed to investigate the protective role of gold nanoparticles (GNPs) on the brain of mice infected with Schistosoma mansoni. Characterizations of GNPs were determined by using high-resolution transmission electron microscopy. Three doses of GNPs (0.25, 0.5, and 1.0 mg/kg body weight) were used to treat animals after S. mansoni infection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 53 publications
(51 reference statements)
4
34
0
Order By: Relevance
“…On the other hand, treatment with SeNPs and GNPs to schistosome infected mice decreased the jejunal oxidative stress significantly. Our results are in agreement with Dkhil et al, 2015a, Dkhil et al, 2015b, Dkhil et al, 2016a, Dkhil et al, 2016b, Dkhil et al, 2017, and Bhattacharjee et al (2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…On the other hand, treatment with SeNPs and GNPs to schistosome infected mice decreased the jejunal oxidative stress significantly. Our results are in agreement with Dkhil et al, 2015a, Dkhil et al, 2015b, Dkhil et al, 2016a, Dkhil et al, 2016b, Dkhil et al, 2017, and Bhattacharjee et al (2017).…”
Section: Discussionsupporting
confidence: 94%
“…Antischistosomal role of selenium nanoparticles (SeNPs) against hepatic injury in mice was demonstrated by Dkhil et al (2016a), additionally, the team has presented the antischistosomal activity of gold nanoparticles (GNPs) in different tissues of mice e.g. liver, brain, kidney and spleen respectively (Dkhil et al, 2015a, Dkhil et al, 2015b, Dkhil et al, 2016a, Dkhil et al, 2016b, Dkhil et al, 2017, Pica-Mattoccia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AuNPs reduced the hepatic worm burden compared to the infected group. This supports Dkhil et al 32 deduction that treatment of infected schistosome mice with AuNPs reduced the extent of the histological disturbances evident in the brains of infected mice.…”
Section: Discussionsupporting
confidence: 87%
“…34 Neuroschistosomiasis, meanwhile, also induces a reduction in GSH level and an increase in nitrite/nitrate and MDA levels, but it has been shown that injection of AuNPs (0.25, 0.5, and 1 mg/kg) into schistosome-infected mice ameliorates the GSH level and reduces levels of nitrite/nitrate and MDA in the brain tissue. 32 In the present study, injection of AuNPs (0.25, 0.5, and 1 mg/kg) into schistosome-infected mice resulted in a significant downregulation of IL-1β, IL-6, TNF-α, IFN-γ, and iNOS mRNA expressions in hepatic tissue versus infected mice.…”
Section: Discussionsupporting
confidence: 48%